2018
DOI: 10.3892/etm.2018.7024
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of hyperphosphatemia and hyperglycemia on the calcification of cultured human aortic smooth muscle cells

Abstract: Vascular calcification (VC) is common in patients with diabetes and/or chronic kidney disease (CKD). It is strongly associated with cardiovascular morbidity and mortality. Hyperphosphatemia caused by CKD induces the transformation of vascular smooth muscle cells (VSMCs) into chondrocytes or osteoblast-like cells. Hyperglycemia may also accelerate VC. However, the exact mechanisms of this remain unclear. The effects of simultaneous hyperphosphatemia and hyperglycemia require investigation. CKD rat models are ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 27 publications
3
32
0
1
Order By: Relevance
“…From another perspective, due to the complex mechanisms of VC, the authors insist on their premise that the experimental model should be as simple as possible to avoid the potential impact from unassociated components. Previously, human aortic smooth muscle cells were cultured in hyperglycemic and hyperphosphatemic media, and the combined effects of hyperphosphatemia and hyperglycemia were also observed on human aortic smooth muscle cell calcification (34). Regarding the above-mentioned results, it was concluded that there were combined effects of hyperglycemia and hyperphosphatemia on VSMC calcification, and it is considered to be a key explanation for why ESRD patients with diabetes mellitus exhibted shorter survival times/higher mortality rate (3537).…”
Section: Discussionmentioning
confidence: 99%
“…From another perspective, due to the complex mechanisms of VC, the authors insist on their premise that the experimental model should be as simple as possible to avoid the potential impact from unassociated components. Previously, human aortic smooth muscle cells were cultured in hyperglycemic and hyperphosphatemic media, and the combined effects of hyperphosphatemia and hyperglycemia were also observed on human aortic smooth muscle cell calcification (34). Regarding the above-mentioned results, it was concluded that there were combined effects of hyperglycemia and hyperphosphatemia on VSMC calcification, and it is considered to be a key explanation for why ESRD patients with diabetes mellitus exhibted shorter survival times/higher mortality rate (3537).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that high glucose could induce VSMC calcification ( Wang et al, 2019 ), so 25 mM glucose was used in this study. Cell calcification was examined by alizarin red staining, and the results showed that MOVAS cells exposed to 25 mM glucose showed significant calcification, as demonstrated by the increased numbers of deep red calcium nodules ( Figure 3A ).…”
Section: Resultsmentioning
confidence: 99%
“…In accordance with previous reports [ 16 , 17 , 39 ], the present observations show that high glucose directly promotes the osteogenic transdifferentiation of VSMCs, although relatively high glucose concentrations were required. In in vitro models of high glucose-induced VSMC calcification, the glucose levels required to induce a response in VSMCs presumably vary with the different origins of the cells and/or the cell culture medium used in experiments [ 16 , 17 , 39 , 40 ]. The effects of high glucose conditions were not mimicked by mannitol, which has been used as an osmotic control for high glucose-induced VSMC calcification processes [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%